If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12r + -8 = 4 + -12r Reorder the terms: -8 + 12r = 4 + -12r Solving -8 + 12r = 4 + -12r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '12r' to each side of the equation. -8 + 12r + 12r = 4 + -12r + 12r Combine like terms: 12r + 12r = 24r -8 + 24r = 4 + -12r + 12r Combine like terms: -12r + 12r = 0 -8 + 24r = 4 + 0 -8 + 24r = 4 Add '8' to each side of the equation. -8 + 8 + 24r = 4 + 8 Combine like terms: -8 + 8 = 0 0 + 24r = 4 + 8 24r = 4 + 8 Combine like terms: 4 + 8 = 12 24r = 12 Divide each side by '24'. r = 0.5 Simplifying r = 0.5
| 10-6x+3=x | | 10a+13=20a+16 | | (y/2)-2=2 | | 8j=10+10j | | 2x-(x-1)=3x-7 | | -7+X=8-X | | 8(2x+4)=80 | | 6+y=24-2y | | 1/3x-4=3/4x+4 | | 6-8n=-15-5n | | -7+x=8-3 | | 5p=p | | 6y-12=42x | | -4-(-5x)=-3x+1 | | 12x=6-8x | | 6x+10=5x+9 | | T-0.37xt=12.6 | | -6(2x-5)=-54 | | 10-n-6n=1-4n | | ab+bc+ac=abc | | 6x-x=45 | | -6(2x-5)=54 | | f(5)-f(3)f(x)=10x-6 | | 7(3x-4y+7)+5(2x-3y+5)= | | 8t-4t=27+t | | 40-3x=16+9x | | 10-x=3x-30 | | 135=9*h | | 3p^3=0 | | 66-(-32)= | | (3n-1)(4n+1)=0 | | N+4=7.0 |